2018
DOI: 10.1002/hbm.23949
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network modifications in Fabry disease: A resting‐state fMRI study with structural correlations

Abstract: Aim of the study was to evaluate the presence of Default Mode Network (DMN) modifications in Fabry Disease (FD), and their possible correlations with structural alterations and neuropsychological scores. Thirty-two FD patients with a genetically confirmed diagnosis of classical FD (12 males, mean age 43.3 ± 12.2) were enrolled, along with 35 healthy controls (HC) of comparable age and sex (14 males, mean age 42.1 ± 14.5). Resting-State fMRI data were analyzed using a seed-based approach, with six different see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…Indeed, the above-mentioned decreased mean diffusivity values were also coupled to a reduced fractional anisotropy throughout the brain of FD patients [ 65 ]. Similarly, a large microstructural WM involvement was recently confirmed by a combined TBSS-functional MRI (fMRI) study, in which extensive areas of reduced fractional anisotropy were found in FD patients, despite the low incidence and load of WMH [ 63 ]. These areas included different supratentorial and infratentorial WM regions, with a relative sparing of only few brain regions [ 63 ], and were correlated to functional cortical changes, denoting the complexity of physiopathological mechanisms of cerebral involvement in FD [ 63 ] (Fig.…”
Section: Advanced Imagingmentioning
confidence: 85%
See 2 more Smart Citations
“…Indeed, the above-mentioned decreased mean diffusivity values were also coupled to a reduced fractional anisotropy throughout the brain of FD patients [ 65 ]. Similarly, a large microstructural WM involvement was recently confirmed by a combined TBSS-functional MRI (fMRI) study, in which extensive areas of reduced fractional anisotropy were found in FD patients, despite the low incidence and load of WMH [ 63 ]. These areas included different supratentorial and infratentorial WM regions, with a relative sparing of only few brain regions [ 63 ], and were correlated to functional cortical changes, denoting the complexity of physiopathological mechanisms of cerebral involvement in FD [ 63 ] (Fig.…”
Section: Advanced Imagingmentioning
confidence: 85%
“…Possible regional differences in GM volume have also been investigated in FD patients, mostly by means of voxel-based morphometry (VBM) analysis. Different VBM studies have been conducted in FD patients in recent years, mostly showing that no differences in terms of regional GM density were present in FD patients compared to healthy controls [ 63 , 65 , 68 , 80 ].…”
Section: Advanced Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased DMN integrity and activation in the anterior module is associated with depressive rumination and anxiety [65] [66]. Other somatic illnesses that result in altered DMN function include obesity [67], sleep apnea [68], respiratory disorders [69], gastrointestinal disorders [70], cardiac/vascular disorders [71], and others [72]. In our perspective, the abnormal DMN state of these disorders can be explained by the altered non-neural processes of the body which then influence the brain.…”
Section: The Default Mode Networkmentioning
confidence: 99%
“…Often, those glycolipid deposits lead to alterations in cerebral vessels and the formation of microstructural damage (i.e., microbleeds) in different brain regions (Tagliavini et al, 1982 ; Reisin et al, 2011 ; Paavilainen et al, 2013 ; Kono et al, 2016 ). In line with these pathologies, different forms of cognitive deficits have been reported in FD patients, spanning from higher prevalence of depression and anxiety to impairment of information processing and attention (Schermuly et al, 2011 ; Bolsover et al, 2014 ; Sigmundsdottir et al, 2014 ), as well as impaired long-term verbal memory (Cocozza et al, 2018 ). These are reflected to some extent in a transgenic FD mouse model which shows increased anxiety-like behavior (Hofmann et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%